Avaliação da atividade de telomerase em células-tronco embrionáriasindiferenciadas e em células neoplásicas de camundongo - Francisco de Assis Nunes Pereira (2008)
Telomerase is an enzyme which plays a role in the maintenance of theproliferation ability of the cells and in the protection and stabilization of thechromosomes. The main function of telomerase is to add telomere sequences at the end of each chromosome, protecting it from DNA damage, and functioning as a biological clock, limiting the maximum number of divisions each cell can undergo. The telomerase activity (TA) can be detected in highly replicative cells, like stem cells and cancer cells, but not in the majority of the differentiated cells of the human organism. The study of telomerase can result in efficient forms ofcontrolling the cell proliferation ability, can also be useful both in the treatment of cancer and also in the researches concerning stem cell therapy. The purpose of this study is to evaluate the TA in different passages of mouse embryonic stem cells (mESC) and to compare the TA of the mESC with mouse neoplastic cells. TRAP-ELISA method was used in a semiquantitative evaluation of TA. Three mESC lineages were evaluated, named CT2, CT3 and CT4 respectively, in three different passages (P13, P15 and P19) each one. All the samples were evaluatedaccording to the presence of undifferentiation markers (genes OCT4 and NANOG) All the samples were evaluated according to the presence of undifferentiation markers (genes OCT4 and NANOG). The cancer cells evaluated were B16F1 (melanoma); B16F10 (metastatic melanoma) and CT26WT (colon carcinoma). The results are expressed as percentage in conformity with a standard of highly known TA.. The CT2 showed 1.09%, 13.24% and 36.90% in P13, P15 and P19 respectively. The CT3 showed 1.46%, 21.82% and 22.37% in P13, P15 and P19 respectively. The CT4 showed 3.82%, 39.05% and 34.22% respectively. The mean TA of the three mESC lineages was 1.59% in P13, 18.53% in P15 and 23.37% in P19. The cancer lineages B16F1, B16F10 e CT26WT showed 128.60%, 1.45% and 30.94% respectively. The results obtained demonstrated allthe samples with high TA. The three passages of mESC showed a tendency of increase in TA and subsequent stabilization. The cancer lineages showed more variable TA values. The results achieved after data analysis let us conclude that both mESC and cancer lineages demonstrate a high capacity of proliferation, due to the high values of TA found in this study.